Temporal Characterization of Microglia/Macrophage Phenotypes in a Mouse Model of Neonatal Hypoxic-Ischemic Brain Injury - Hellström Erkenstam, Nina; Smith, Peter L. P.; Fleiss, Bobbi; Nair, Syam; Svedin, Pernilla; Wang, Wei; Boström, Martina; Gressens, Pierre; Hagberg, Henrik; Brown, Kelly L.; Sävman, Karin; Mallard, Carina (Frontiers in Cellular Neuroscience, 2016)
Immune cells display a high degree of phenotypic plasticity, which may facilitate their participation in both the progression and resolution of injury-induced inflammation. The purpose of this study was to investigate the temporal expression of genes associated with classical and alternative polarization phenotypes described for macrophages and to identify related cell populations in the brain following neonatal hypoxia-ischemia (HI). HI was induced in 9-day old mice and brain tissue was collected up to 7 d post-insult to investigate expression of genes associated with macrophage activation. Using cell-markers, CD86 (classic activa-tion) and CD206 (alternative activation), we assessed temporal changes of CD11b+ cell populations in the brain and studied the protein expression of the immunomodulatory factor galectin-3 in these cells. HI induced a rapid regulation (6h) of genes associated with both classical and alternative polarization phenotypes in the injured hemisphere. FACS analysis showed a marked increase in the number of CD11+CD86+ positive cells at 24 h after HI (+3,667 %), which was coupled with a relative suppression of CD11+CD206+ cells and cells that did not express either CD86 or CD206. The CD11+CD206+ popula-tion was mixed with some cells also expressing CD86. Confocal microscopy confirmed that a subset of cells expressed both CD86 and CD206, particularly in injured grey and white matter. Protein con-centration of galectin-3 was markedly increased mainly in the cell population lacking CD86 or CD206 in the injured hemisphere. These cells were predominantly resident microglia as very few galectin-3 positive cells co-localized with infiltrating myeloid cells in Lys-EGFP-ki mice after HI. In summary, HI was characterized by an early mixed gene response, but with a large expansion of mainly the CD86 positive population during the first day. However, the injured hemisphere also con-tained a subset of cells expressing both CD86 and CD206 and a large population that expressed nei-ther activation marker CD86 nor CD206. Interestingly, these cells expressed the highest levels of ga-lectin-3 and were found to be predominantly resident microglia. Galectin-3 is a protein involved in chemotaxis and macrophage polarization suggesting a novel role in cell infiltration and immuno-modulation for this cell population after neonatal injury.